Primary cutaneous nocardiosis - Vikrant A Saoji; Sandhya V Saoji; Rutuja W Gadegone; Priyanka R Menghani (Wolters Kluwer Medknow Publications, 2012)
A 35-year-old male presented with multiple discharging sinuses and fluctuant swelling on right side of face which started after a vehicular accident three year back. The lesions did not respond to routine antibiotics treatment but went on increasing. Gram smear showed typical acid fast branching filaments suggestive of nocardiosis, which was confirmed by culture. Patient received co-trimoxazole for three and a half month. When seen again after three years, all the lesions had healed with puckered scarring. Patient had received co-trimoxazole for three and a half months with dramatic improvement.